Feasibility Study of Wind Energy Generation Systems in Masirah Island: Real Case Study - Ismail F.B.; Mahdi M.N.; Salah A.A.; Al-Muhsen N.F.O.; Shalby M.M.; Al Nafie Y.K. (Institute of Electrical and Electronics Engineers Inc., 2023)
Diesel engines; Digital storage; Energy policy; Sea level; Solar energy; Weibull distribution; Wind; Case-studies; Diesel generators; Feasibility studies; Generation systems; Hybrid power; Hybrid power system; Rayleigh parameters; Real case; Renewable energies; Wind energy generation; Wind power